Real-Time Thickness Measurement of Marine Oil Spill by Fiber-Optic Surface Plasmon Resonance Sensors - Yin, Huiting; Chen, Shaohuang; Huang, Renliang; Chang, Heng; Liu, Jiayue; Qi, Wei; He, Zhimin; Su, Rongxin (Frontiers in Marine Science, 2022)
At present, marine oil spills occur frequently, putting forward higher requirements for rapidly detection. Measurements of oil slick thickness is highly associated with hazard assessment of the oil leak. In this study, the gold-film fiber optic surface plasmon resonance (FOSPR) sensor prepared by polydopamine accelerated wet chemical plating can rapidly and real time measure oil slick thickness. The FOSPR sensor has a sensitivity of −1.373 %/mm in the thickness range of 0−5 mm at water−oil interface and a sensitivity of −2.742 %/mm in the thickness ranging from 0 to 10 mm at air−oil interface. No significant effect of temperature and salinity was found on the oil slick thickness measurement. Furthermore, the fabricated FOSPR sensor has favorable renewability renewable and reusability which have great potential in marine oil slick thickness estimation.